AN ANALYSIS OF STUDENTS ABILITY IN APPLYING ADJECTIVE ORDER IN DESCRIPTIVE TEXT - Rahel Lolita Ginting; Sonia Agnes Theresia; Marniati Ndruru; Rahmawati Rahmawati (English Education Journal, 2020)
Writing is an ability to be able to express their opinions through an article. Writing models have many forms and kinds. Descriptive text is one of them. Descriptive text is text whose content aims to explain a thing, whether it's about a person, an object or a certain condition whose characteristics need to be explained. Researchers see that problems emerge among students in writing descriptive texts. This problem is seen from the ability of students who are still considered lacking in describing a matter in descriptive text. From there researchers moved to conduct research using qualitative research methods to see and examine the problems that occur and strive to resolve existing problems. And from the results of research that researchers have done, researchers found several factors classified through the analysis model, namely related to students' problems in seeing details of a matter, lack of vocabulary used, to the lack of knowledge about grammar related to adjective order. The researcher concludes that this problem is a problem that needs and is worth studying. It aims to develop a newer educational model for later research with this research which is used as a reference and or reference for future researchers.